TiAlN coated cutting tool and preparation method thereof

By using a TiAlN coating structure composed of a TiAlN bonding layer and a TiCN layer on the tool, and using carbon and nitrogen co-doped titanium targets to deposit the TiCN layer, the problem of insufficient wear resistance of traditional coating tools is solved, and the wear resistance and binding strength are significantly improved.

CN119615057APending Publication Date: 2025-03-14JIANGSU TIANGONG CEMENTED CARBIDE TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411795823.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Traditional coated tools lack wear resistance and have a short service life.

Method used

Using a TiAlN coating tool with a TiAlN binding layer and a TiCN layer arranged on the substrate surface from the inside to the outside, a TiAlN coating tool was used to deposit carbon and nitrogen co-doped titanium targets on the surface of the TiAlN binding layer through the PVD process to obtain a TiCN layer.

Benefits of technology

Improves the wear resistance and coating bonding of coated tools, and extends service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005176663910000091
    Figure BDA0005176663910000091
Patent Text Reader

Abstract

The invention relates to the technical field of metal cutting tools, in particular to a TiAlN coated tool and a preparation method thereof. The TiAlN coated cutting tool is prepared through the following preparation steps that a carbon and nitrogen co-doped titanium target material is prepared; pretreating the matrix; a TiAlN bonding layer is deposited; and depositing a TiCN layer. Compared with a traditional coating tool formed by directly depositing a TiC target material on the surface of a TiAlN binding layer, the coating tool obtained through the preparation method has excellent wear resistance, cutting force and coating binding force, in the actual application process, the blade abrasion loss is small, in the cutting process, the coating falling phenomenon cannot occur, and the service life is long.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal cutting tools, and in particular to a TiAlN coating tool and a preparation method thereof. Background Art

[0002] With the continuous advancement of materials science and manufacturing, machining has higher and higher requirements for cutting speed and cutting accuracy, and tool coatings have also developed rapidly.

[0003] The tool coating is deposited on the tool surface, which can effectively protect the tool cutting surface, reduce wear, extend the tool life cycle, and at the same time improve processing quality and cutting efficiency.

[0004] Titanium aluminum nitride (TiAlN) coating has the characteristics of low internal stress, high hardness, low thermal conductivity, good high-temperature oxidation resistance, and good red hardness. In particular, the high-aluminum-content TiAlN hard coating exhibits excellent high-temperature oxidation resistance, making it suitable for high-speed cutting.

[0005] Patent technology document CN116180006A discloses a TiAlN / CrAlLaBN composite coating, a preparation method thereof, and a tool. The TiAlN / CrAlLaBN composite coating includes a TiAlN bonding layer, a TiAlN / CrAlLaBN transition layer, and a CrAlLaBN top layer, which are sequentially arranged on the surface of the substrate from the inside to the outside. Through the combination of the above three layers, the prepared composite coating has a certain hardness, high toughness and coating bonding strength, and excellent comprehensive performance, which can meet the subsequent stringent application scenario requirements. However, in actual use, the wear resistance of the coating is still lacking, and the service life is short. Summary of the invention

[0006] In view of this, the purpose of the present invention is to provide a TiAlN coated tool and a preparation method thereof, so as to solve the problem that the traditional coated tools are lacking in wear resistance.

[0007] Based on the above purpose, the present invention provides a TiAlN coated tool, comprising a TiAlN bonding layer and a TiCN layer sequentially arranged on the surface of a substrate from the inside to the outside.

[0008] The TiCN layer is obtained by depositing carbon and nitrogen co-doped titanium targets on the surface of the TiAlN bonding layer through a PVD process;

[0009] The steps for preparing the carbon and nitrogen co-doped titanium target are as follows:

[0010] S1: dispersing titanium powder in deionized water to obtain a titanium powder dispersion, adjusting the pH to 4-5, adding graphene oxide, stirring evenly, and drying to obtain titanium powder loaded with graphene oxide;

[0011] S2: mixing titanium powder loaded with graphene oxide, ethanol and dicyandiamide, drying and heat-insulating to obtain nitrogen-doped graphene / titanium powder;

[0012] S3: The nitrogen-doped graphene / titanium powder is subjected to ball milling, cold pressing, sintering and hot pressing to obtain a carbon and nitrogen co-doped titanium target.

[0013] Furthermore, in step S1, the weight ratio of the titanium powder to the graphene oxide is 10:0.1-0.2.

[0014] Furthermore, the particle size of the titanium powder in step S1 is 10-100 nm.

[0015] Furthermore, the flake size of the graphene oxide in step S1 is 1-4 nm, and the number of flake layers is ≤10.

[0016] Furthermore, in step S2, the usage ratio of dicyandiamide, titanium powder loaded with graphene oxide and ethanol is 0.2-0.4g:10g:500-700ml.

[0017] Furthermore, the insulation temperature in step S2 is 300-400° C., and the insulation time is 2-4 hours.

[0018] Furthermore, in step S3, the rotation speed of the ball mill is 500-700 rpm, and the ball milling time is 10-12 h.

[0019] Furthermore, the cold pressing pressure in step S3 is 160MPa-220MPa, the specific sintering process is first at 900-950°C, keeping warm for 3-8h, then at 1200-1250°C, keeping warm for 3-6h, the hot isostatic pressing pressure is 100-160MPa, and the temperature is 1000-1200°C.

[0020] Furthermore, the TiAlN layer includes the following elements in atomic percentage: Ti 16-23 at.%, Al 20-30 at.%, and N 50-60 at.%.

[0021] Furthermore, the present invention also provides a method for preparing a TiAlN coated tool, comprising the following steps:

[0022] (1) preparing carbon and nitrogen co-doped titanium targets;

[0023] (2) Substrate pretreatment: After cleaning and drying the substrate, place it in a vacuum coating device and adjust the vacuum degree of the device to 8×10 -5 mbar, heated to a temperature of 460-480°C;

[0024] (3) Deposition of TiAlN bonding layer: vapor deposition of TiAlN bonding layer on the substrate surface;

[0025] (4) Deposition of TiCN layer: vapor deposition of TiCN layer on the surface of TiAlN bonding layer.

[0026] Furthermore, the process parameters for depositing the TiAlN bonding layer are as follows: N2 gas flow rate is 800-950sccm, chamber pressure is 2-5Pa, TiAl target current is 100-150A, workpiece support bias is -80-120V, and deposition time is 30-90min.

[0027] Furthermore, the thickness of the TiAlN bonding layer is 0.5-1 μm.

[0028] Furthermore, the atomic percentage content of the TiAl target is: Ti: 45 at.%, Al: 55 at.%.

[0029] Furthermore, the process parameters for depositing the TiCN layer are as follows: N2 gas flow rate is 800-950sccm, chamber pressure is 2-5Pa, carbon and nitrogen co-doped titanium target current is 130-180A, workpiece support bias is -100--140V, and deposition time is 5-15min.

[0030] Furthermore, the thickness of the TiCN top layer is 0.2-0.5 μm.

[0031] Beneficial effect: The present invention adopts carbon and nitrogen co-doped titanium target material. Nitrogen doping can form more titanium nitride reinforcement phase, and this reinforcement phase can be evenly distributed on the coating surface, so that its wear resistance and the bonding strength between the coatings are improved.

[0032] The present invention adopts graphene for doping to obtain a carbon and nitrogen co-doped titanium target material. The graphene itself has high hardness, self-lubricating properties, certain adhesive properties and a lamellar structure, so that the wear resistance of the coated tool and the coating bonding force are further improved.

[0033] The present invention deposits carbon and nitrogen co-doped titanium targets, which can significantly improve the wear resistance, cutting force and coating bonding strength of the coated tool compared to the conventional process of depositing TiC targets. DETAILED DESCRIPTION

[0034] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0035] Embodiment 1: A TiAlN coated tool, the specific preparation steps are as follows:

[0036] (1) dispersing 10 g of titanium powder in 400 ml of deionized water to obtain a titanium powder dispersion, adjusting the pH to 4, adding 0.1 g of graphene oxide, stirring evenly with a magnetic stirrer, heating and drying, and obtaining titanium powder loaded with graphene oxide;

[0037] (2) dissolving 0.2 g of dicyandiamide in 500 ml of ethanol, adding 10 g of titanium powder loaded with graphene oxide, stirring evenly, heating and drying, and keeping warm at 300° C. for 2 h to obtain nitrogen-doped graphene / titanium powder;

[0038] (3) The nitrogen-doped graphene / titanium powder was ball-milled at 500 rpm for 10 h, poured into a mold, pressed at 160 MPa, then placed in an argon atmosphere at 900 ° C for 3 h, then at 1200 ° C for 3 h, and finally hot isostatically pressed at 100 MPa and 1000 ° C. After cooling, a carbon and nitrogen co-doped titanium target was obtained;

[0039] (4) The carbide tool was ultrasonically cleaned in anhydrous ethanol and deionized water for 25 min respectively, and then taken out and dried in an oven at 110° C. for 1 h;

[0040] (5) Place the pretreated carbide tool in the vacuum coating equipment and adjust the vacuum degree of the equipment to 8×10 - 5 mbar, heated to 460°C;

[0041] (6) Open the nitrogen valve, the N2 gas flow rate is 800 sccm, the chamber pressure is 2 Pa, the TiAl target current is 100 A, the workpiece support bias is -80 V, the TiAl target is ignited, and the deposition time is 30 min;

[0042] (7) Ensure the deposition atmosphere in step (6), turn off the TiAl target, set the N2 gas flow rate to 800 sccm, the chamber pressure to 2 Pa, the carbon and nitrogen co-doped titanium target current to 130 A, the workpiece support bias to -100 V, ignite the carbon and nitrogen co-doped titanium target, and the deposition time to 5 min to obtain a TiAlN coated tool.

[0043] Embodiment 2: A TiAlN coated cutting tool, the specific preparation steps are as follows:

[0044] (1) dispersing 10 g of titanium powder in 450 ml of deionized water to obtain a titanium powder dispersion, adjusting the pH to 5, adding 0.15 g of graphene oxide, stirring evenly with a magnetic stirrer, heating and drying, and obtaining titanium powder loaded with graphene oxide;

[0045] (2) dissolving 0.3 g of dicyandiamide in 600 ml of ethanol, adding 10 g of titanium powder loaded with graphene oxide, stirring evenly, heating and drying, and keeping warm at 350° C. for 3 h to obtain nitrogen-doped graphene / titanium powder;

[0046] (3) The nitrogen-doped graphene / titanium powder was ball-milled at 600 rpm for 11 h, poured into a mold, pressed at 200 MPa, and then placed in an argon atmosphere at 930 ° C. for 5 h, then at 1230 ° C. for 4 h, and finally hot isostatically pressed at 130 MPa and 1100 ° C. After cooling, a carbon and nitrogen co-doped titanium target was obtained;

[0047] (4) The carbide tool was ultrasonically cleaned in anhydrous ethanol and deionized water for 25 min respectively, and then taken out and dried in an oven at 110° C. for 1 h;

[0048] (5) Place the pretreated carbide tool in the vacuum coating equipment and adjust the vacuum degree of the equipment to 8×10 - 5 mbar, heated to 470°C;

[0049] (6) Open the nitrogen valve, the N2 gas flow rate is 850 sccm, the chamber pressure is 3 Pa, the TiAl target current is 120 A, the workpiece support bias is -100 V, the TiAl target is ignited, and the deposition time is 60 min;

[0050] (7) Ensure the deposition atmosphere in step (6), turn off the TiAl target, set the N2 gas flow rate to 850 sccm, the chamber pressure to 4 Pa, the carbon and nitrogen co-doped titanium target current to 150 A, the workpiece support bias to -120 V, ignite the carbon and nitrogen co-doped titanium target, and the deposition time to 10 min to obtain a TiAlN coated tool.

[0051] Embodiment 3: A TiAlN coated tool, the specific preparation steps are as follows:

[0052] (1) dispersing 10 g of titanium powder in 500 ml of deionized water to obtain a titanium powder dispersion, adjusting the pH to 5, adding 0.2 g of graphene oxide, stirring evenly with a magnetic stirrer, heating and drying, and obtaining titanium powder loaded with graphene oxide;

[0053] (2) dissolving 0.4 g of dicyandiamide in 700 ml of ethanol, adding 10 g of titanium powder loaded with graphene oxide, stirring evenly, heating and drying, and keeping warm at 400° C. for 4 h to obtain nitrogen-doped graphene / titanium powder;

[0054] (3) The nitrogen-doped graphene / titanium powder was ball-milled at 700 rpm for 12 h, poured into a mold, pressed at 1220 MPa, and then placed in an argon atmosphere at 950 ° C for 8 h, then at 1250 ° C for 6 h, and finally hot isostatically pressed at 160 MPa and 1200 ° C. After cooling, a carbon and nitrogen co-doped titanium target was obtained;

[0055] (4) The carbide tool was ultrasonically cleaned in anhydrous ethanol and deionized water for 25 min respectively, and then taken out and dried in an oven at 110° C. for 1 h;

[0056] (5) Place the pretreated carbide tool in the vacuum coating equipment and adjust the vacuum degree of the equipment to 8×10 - 5 mbar, heated to 480°C;

[0057] (6) Open the nitrogen valve, the N2 gas flow rate is 950 sccm, the chamber pressure is 5 Pa, the TiAl target current is 150 A, the workpiece support bias is -120 V, the TiAl target is ignited, and the deposition time is 90 min;

[0058] (7) Ensure the deposition atmosphere in step (6), turn off the TiAl target, set the N2 gas flow rate to 950 sccm, the chamber pressure to 5 Pa, the carbon and nitrogen co-doped titanium target current to 180 A, the workpiece support bias to -140 V, ignite the carbon and nitrogen co-doped titanium target, and the deposition time to 15 min to obtain a TiAlN coated tool.

[0059] Comparative Example 1: A TiAlN coated tool, which differs from Example 2 in that the carbon-nitrogen co-doped titanium target is replaced with a carbon-doped titanium target, and the specific preparation steps are as follows:

[0060] (1) dispersing 10 g of titanium powder in 450 ml of deionized water to obtain a titanium powder dispersion, adjusting the pH to 5, adding 0.15 g of graphene oxide, stirring evenly with a magnetic stirrer, heating and drying, and obtaining titanium powder loaded with graphene oxide;

[0061] (2) The titanium powder loaded with graphene oxide was ball-milled at 600 rpm for 11 h, poured into a mold, pressed at 200 MPa, then placed in an argon atmosphere at 930 ° C. for 5 h, then at 1230 ° C. for 4 h, and finally hot isostatically pressed at 130 MPa and 1100 ° C. After cooling, a carbon-doped titanium target was obtained;

[0062] The remaining steps are the same as in Example 2.

[0063] Comparative Example 2: A TiAlN coated tool, which differs from Example 2 in that graphene oxide is replaced by carbon powder, and the specific preparation steps are as follows:

[0064] (1) dispersing 10 g of titanium powder in 450 ml of deionized water to obtain a titanium powder dispersion, adjusting the pH to 5, adding 0.15 g of carbon powder, stirring evenly with a magnetic stirrer, heating and drying, and obtaining titanium powder loaded with graphene oxide;

[0065] (2) 0.3 g of dicyandiamide was dissolved in 600 ml of ethanol, and 10 g of carbon-loaded titanium powder was added, stirred evenly, heated and dried, and kept at 350° C. for 3 h to obtain nitrogen-carbon co-doped titanium powder;

[0066] (3) The nitrogen and carbon co-doped titanium powder was ball-milled at 600 rpm for 11 h, poured into a mold, pressed at 200 MPa, and then placed in an argon atmosphere at 930° C. for 5 h, then at 1230° C. for 4 h, and finally hot isostatically pressed at 130 MPa and 1100° C. After cooling, a carbon and nitrogen co-doped titanium target was obtained;

[0067] The remaining steps are the same as in Example 2.

[0068] Comparative Example 3: A TiAlN coated tool, the specific preparation steps are as follows:

[0069] (1) The carbide tool was ultrasonically cleaned in anhydrous ethanol and deionized water for 25 min respectively, and then dried in an oven at 110°C for 1 h;

[0070] (2) Place the pretreated carbide tool in the vacuum coating equipment and adjust the vacuum degree of the equipment to 8×10 - 5 mbar, heated to 470°C;

[0071] (3) Open the nitrogen valve, the N2 gas flow rate is 850 sccm, the chamber pressure is 3 Pa, the TiAl target current is 120 A, the workpiece support bias is -100 V, the TiAl target is ignited, and the deposition time is 60 min;

[0072] (4) Ensure the deposition atmosphere in step (6), close the TiAl target, set the N2 gas flow rate to 850 sccm, the chamber pressure to 4 Pa, the TiC target current to 150 A, the workpiece support bias to -120 V, ignite the TiC target, and deposit for 10 min to obtain a TiAlN coated tool.

[0073] Performance Testing

[0074] Wear resistance: The test was conducted using a CK6140 horizontal lathe produced by Chongqing Honggang CNC Machine Tool Co., Ltd. The experimental standard was: each set of blades continuously moved 220 mm at 100 m / min until the moving distance was L = 2200 mm, and the wear of the flank was measured. The test results are shown in Table 1.

[0075] Cutting force: The Swiss Kistler 9257B force measuring device was used for testing, and the cutting speed was measured at 100 m / min. The test results are shown in Table 1;

[0076] Coating adhesion: The test was conducted using an automatic scratch tester with a speed of 100 N / m, a scratch length of 5 mm, and a final load of 100 N. The test results are shown in Table 1.

[0077] Table 1 Performance test results

[0078]

[0079] Data analysis: It can be seen from Examples 1, 2 and 3 in Table 1 that the TiAlN coated cutting tool of the present invention has excellent wear resistance, cutting force and coating bonding strength.

[0080] It can be seen from Example 2 and Comparative Example 1 in Table 1 that the wear resistance and bonding of the coated tool are improved by adopting carbon and nitrogen co-doped titanium target materials. This is mainly because during the deposition process, on the one hand, the grain structure of the coating can be refined, and on the other hand, more ceramic reinforcement phases such as titanium nitride can be formed, and this reinforcement phase can be evenly distributed on the surface of the coating, so that its wear resistance is improved; and nitrogen doping can promote the interface reaction between the coating and the TiAlN bonding layer, forming a stronger chemical bond, which helps to improve the bonding force between the coating and the TiAlN bonding layer.

[0081] It can be seen from Example 2 and Comparative Example 2 in Table 1 that the present invention improves its wear resistance, coating adhesion and cutting force by using graphene for doping instead of simply doping carbon elements with carbon powder. This is mainly because on the one hand, graphene itself has higher hardness, self-lubricating properties and certain bonding properties, which will make the TiCN layer and the TiAlN layer more tightly combined, thereby further improving the coating adhesion, and also make the tool coating have a lower friction coefficient, so that its wear resistance is further improved; on the other hand, the lamellar structure of graphene can load more nitrogen elements and generate more ceramic reinforcement phases, so that the wear resistance and coating adhesion of the coated tool are further improved.

[0082] It can be seen from Example 2 and Comparative Examples 1, 2 and 3 in Table 1 that the present invention can significantly improve the wear resistance, cutting force and coating bonding strength of the coated tool by depositing carbon and nitrogen co-doped titanium targets compared to the conventional process of depositing TiC targets.

[0083] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

Claims

1. A TiAlN coated tool, characterized in that: It includes a TiAlN bonding layer and a TiCN layer which are sequentially arranged on the surface of the substrate from the inside to the outside; The TiCN layer is obtained by depositing carbon and nitrogen co-doped titanium targets on the surface of the TiAlN bonding layer through a PVD process; The steps for preparing the carbon and nitrogen co-doped titanium target are as follows: S1: dispersing titanium powder in deionized water to obtain a titanium powder dispersion, adjusting the pH to 4-5, adding graphene oxide, stirring evenly, and drying to obtain titanium powder loaded with graphene oxide; S2: mixing titanium powder loaded with graphene oxide, ethanol and dicyandiamide, drying and heat-insulating to obtain nitrogen-doped graphene / titanium powder; S3: The nitrogen-doped graphene / titanium powder is subjected to ball milling, cold pressing, sintering, and hot pressing to obtain a carbon-nitrogen co-doped titanium target; The weight ratio of titanium powder to graphene oxide in step S1 is 10:0.1-0.2; The usage ratio of dicyandiamide, titanium powder loaded with graphene oxide and ethanol in step S2 is 0.2-0.4g:10g:500-700ml.

2. The TIAIN coated tool according to claim 1, characterized in that: The TiAlN layer includes elements having the following atomic percentage contents: Ti 16-23 at.%, Al 20-30 at.%, and N 50-60 at.%.

3. The TiAlN coated tool according to claim 1, characterized in that: The pressure of the cold pressing in step S3 is 160MPa-220MPa, the specific sintering process is first at 900-950℃, keeping warm for 3-8h, then at 1200-1250℃, keeping warm for 3-6h, the pressure of the hot pressing is 100-160MPa, and the temperature is 1000-1200℃.

4. A method for preparing a TiAlN coated tool according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) preparing carbon and nitrogen co-doped titanium targets; (2) Substrate pretreatment: After cleaning and drying the substrate, place it in a vacuum coating equipment, adjust the vacuum degree of the equipment to 8×10-5mbar, and heat it to a temperature of 460-480°C; (3) Deposition of TiAlN bonding layer: vapor deposition of TiAlN bonding layer on the substrate surface; (4) Deposition of TiCN layer: vapor deposition of TiCN layer on the surface of TiAlN bonding layer.

5. The method for preparing a TiAlN coated tool according to claim 4, characterized in that: The process parameters for depositing the TiAlN bonding layer in step (3) are as follows: N2 gas flow rate is 800-950sccm, chamber pressure is 2-5Pa, TiAl target current is 100-150A, workpiece support bias is -80-120V, and deposition time is 30-90min.

6. The method for preparing a TiAlN coated tool according to claim 4, characterized in that: The process parameters for depositing the TiCN layer in step (4) are as follows: N2 gas flow rate is 800-950sccm, chamber pressure is 2-5Pa, carbon and nitrogen co-doped titanium target current is 130-180A, workpiece support bias is -100--140V, and deposition time is 5-15min.

Citation Information

Patent Citations

  • TiAlN / CrAlLaBN composite coating, preparation method thereof and cutter

    CN116180006A